2022
DOI: 10.1136/bjsports-2021-104749
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence and risk factors for low back pain in adolescent athletes: a systematic review and meta-analysis

Abstract: ObjectiveTo investigate the incidence, prevalence, risk factors and morphological presentations of low back pain (LBP) in adolescent athletes.DesignSystematic review with meta-analysis.Data sourcesMedline, Embase, CINAHL via EBSCO, Web of Science, Scopus.Eligibility criteria for selecting studiesStudies evaluating the incidence and/or prevalence of LBP in adolescent athletes across all sports.ResultsThere were 80 studies included. The pooled incidence estimate of LBP in adolescent athletes was 11% (95% CI 8% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 109 publications
(367 reference statements)
0
14
0
1
Order By: Relevance
“…Two corresponding authors were contacted to request information to decide if these studies checked our inclusion criteria. (Chikte et al, 2011; Wall et al, 2022) Both studies were excluded. The study selection process is reported in Figure 1 and the list of excluded studies during the analysis at full text appears in Supplementary File 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Two corresponding authors were contacted to request information to decide if these studies checked our inclusion criteria. (Chikte et al, 2011; Wall et al, 2022) Both studies were excluded. The study selection process is reported in Figure 1 and the list of excluded studies during the analysis at full text appears in Supplementary File 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the significance of variables derived from studies that defined outcomes as varied as LBP in the absence of radiology [ 48 , 50 , 57 , 58 , 61 , 62 ], radiological abnormalities in the absence of LBP [ 43 , 53 56 , 65 ], or a combination of LBP, abnormal radiology and missed playing time [ 42 , 44 47 , 51 , 52 , 59 , 60 , 63 , 64 ] is problematic. Whilst the appearance of LBP has been reported to be a common finding in fast bowlers without accompanying missed playing time [ 9 ]; spondylolysis is the most common cause of LBP in young athletes [ 106 ], and LBSI should be suspected in a fast bowler presenting with LBP contralateral to their bowling arm side [ 12 ]. The significance of LBP as a surrogate for lumbar spine injury in fast bowlers is yet to be determined due to previously described attrition biases in the published literature [ 41 – 43 , 45 50 , 53 , 60 , 61 , 65 ], and studies being cross sectional [ 54 56 , 62 , 63 ], retrospective [ 57 61 , 64 ], or prospective with limited follow up periods [ 42 , 46 50 , 52 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain (LBP) is a serious social health and clinical problem which impact over 80% people in the world during their lifetime at some point, especially for the elderly 1-3 . However, it has shown a trend of affecting younger patients recently.…”
Section: Introductionmentioning
confidence: 99%